The pious man and his sons - Khan, Saniyasnain; Anand, Achla Anand, Achal K. (Goodword Books New Delhi, 2009)
Yūsuf (Joseph) son of the Prophet Yaqub (Jacob) is betratyed by his jealous brothers and sold to an Egyptian prince